Testing an ethnographic analogy through geometric morphometrics: A comparison between ethnographic arrows and archaeological projectile points from Late Holocene Fuego-Patagonia - Charlin, Judith Emilce (2018)
Under certain conditions, ethnographic analogies can help to shed light on past behaviors registered in the archaeological record via observation and model-building from modern societies. In this context, ethnographic weapons are often used as morphometric models to assign a given function to archaeological projectile points. For southern Patagonia, J. Bird proposed a functional analogy between arrows used by the Ona (also known as Selk'nam), a hunter-gatherer group that inhabited northern Tierra del Fuego during historical epochs, and the type V Late Holocene projectile points from southern continental Patagonia. Based on the similarity in terms of small size and shape attributes between the type V archaeological points and Ona (Selk'nam) ethnographic arrows, Bird proposed that the former were arrow points. Here we test the morphometric analogy based on comparisons of size and shape variables defining Ona (Selk'nam) arrows from museum ethnographic collections, and type V projectile points from southern Patagonia archaeological sites. Then, we assess the relative importance of projectile point reduction as a source of morphometric variation. We compared both, archaeological and ethnographic points using geometric morphometrics and multivariate statistical analyses. Results showed significant shape differences between ethnographic and archaeological samples before and after controlling for size and reduction parameters, suggesting that both kinds of points had different designs and life histories. However, when spear-like points are included in the comparison, Ona (Selk'nam) and type V points tend to cluster together. The results obtained from this broader comparison framework suggest that, when functional diversity and reduction effects are taken into account, ethnographic weapons can be considered as useful morphometric models to infer the function of archaeological points. Our results highlight the importance of considering similarities in environment, subsistence, mobility, tool design constraints, and lithic characteristics prior any extrapolation based on ethnographic analogies.